2019
DOI: 10.1111/jbi.13493
|View full text |Cite
|
Sign up to set email alerts
|

A synthesis of animal‐mediated seed dispersal of palms reveals distinct biogeographical differences in species interactions

Abstract: Aim:To synthesize published knowledge on palm-frugivore seed dispersal observations and to test whether broad-scale differences in geographic coverage, diversity, composition and functional structure of plant-animal interactions emerge between biogeographical regions.Location: Neotropics and Afrotropics. Methods:We constructed a meta-network for both regions by aggregating observations of pairwise palm-frugivore interactions from the primary literature. We assessed sampling completeness with accumulation curve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
42
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 198 publications
(121 reference statements)
1
42
2
Order By: Relevance
“…The palms are a characteristic element of tropical habitats (Couvreur & Baker, 2013; Kissling et al, 2012) and their fruits are a keystone resource for the tropical fauna (Fleming & Kress, 2013). The great morphological diversity in palm fruits and seeds (Figure 1a‐c) (Henderson et al, 1995) allows seed dispersal by a wide range of frugivores, from small songbirds to elephants and tapirs (Muñoz, Trøjelsgaard, & Kissling, 2019; Zona & Henderson, 1989). This variety of morphological characteristics and interactions can be roughly mapped into two main seed‐dispersal syndromes: small‐colourful fruits dispersed mainly by birds and large‐dull‐coloured fruits dispersed mainly by mammals.…”
Section: Introductionmentioning
confidence: 99%
“…The palms are a characteristic element of tropical habitats (Couvreur & Baker, 2013; Kissling et al, 2012) and their fruits are a keystone resource for the tropical fauna (Fleming & Kress, 2013). The great morphological diversity in palm fruits and seeds (Figure 1a‐c) (Henderson et al, 1995) allows seed dispersal by a wide range of frugivores, from small songbirds to elephants and tapirs (Muñoz, Trøjelsgaard, & Kissling, 2019; Zona & Henderson, 1989). This variety of morphological characteristics and interactions can be roughly mapped into two main seed‐dispersal syndromes: small‐colourful fruits dispersed mainly by birds and large‐dull‐coloured fruits dispersed mainly by mammals.…”
Section: Introductionmentioning
confidence: 99%
“…In summary, our results agree with Howe's (1985) critical view that the megafaunal syndrome hypothesis suffers from a general lack of knowledge on the natural history of seed dispersal of many large-fruited plants. A knowledge gap in the number of interactions between Neotropical palms and vertebrates has been recently highlighted (Muñoz et al, 2019). For instance, Donatti et al (2007) expressed their surprise about the survival of some plant species, exemplified by the apparent lack of contemporary dispersers and dispersal mechanisms in A. speciosa, and only three interactions with frugivorous species have been recorded for this palm in a recent review (Muñoz et al, 2019).…”
Section: External Dispersal As a Key Mechanism For Large-fruited Plantsmentioning
confidence: 99%
“…A knowledge gap in the number of interactions between Neotropical palms and vertebrates has been recently highlighted (Muñoz et al, 2019). For instance, Donatti et al (2007) expressed their surprise about the survival of some plant species, exemplified by the apparent lack of contemporary dispersers and dispersal mechanisms in A. speciosa, and only three interactions with frugivorous species have been recorded for this palm in a recent review (Muñoz et al, 2019). However, we found that this palm is extensively dispersed primarily by a large macaw (Ara ararauna) and at least by seven secondary ground-and tree-dwelling dispersers, including rodents (see b Despite no fruit consumption, feces evaluated for the presence of seeds of other palm species confirmed the lack of seed dispersal.…”
Section: External Dispersal As a Key Mechanism For Large-fruited Plantsmentioning
confidence: 99%
See 2 more Smart Citations